2018
DOI: 10.1002/mgg3.467
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing identifies novel predisposing genes in neural tube defects

Abstract: Background Neural tube defects (NTD) are among the most common defects affecting 1:1000 births. They are caused by a failure of neural tube closure during development. Their clinical presentation is diverse and dependent on the site and severity of the original defect on the embryonic axis. The etiology of NTD is multifactorial involving environmental factors and genetic variants that remain largely unknown. Methods We have conducted a whole exome sequencing (WES) study in five new NTD families and pooled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…These insights add to our existing knowledge of the genetic mechanisms underlying NTDs development [17]. The ongoing genomic revolution will indeed offer the possibility to carry out genomic projects, with the aim of identifying new variants implicated in the biologic basis of NTDs [16][17][18]. The low rate of NTDs observed in our case series, even more marked than that currently found in HICs [8,[19][20][21], may be explained by some plausible factors: a likely high number of prenatal diagnoses and abortions in our setting, and the phenomenon of health emigration (from Sicily to central-northern Italian regions), that may have contributed to the reduction/underestimation of our cases.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These insights add to our existing knowledge of the genetic mechanisms underlying NTDs development [17]. The ongoing genomic revolution will indeed offer the possibility to carry out genomic projects, with the aim of identifying new variants implicated in the biologic basis of NTDs [16][17][18]. The low rate of NTDs observed in our case series, even more marked than that currently found in HICs [8,[19][20][21], may be explained by some plausible factors: a likely high number of prenatal diagnoses and abortions in our setting, and the phenomenon of health emigration (from Sicily to central-northern Italian regions), that may have contributed to the reduction/underestimation of our cases.…”
Section: Discussionmentioning
confidence: 80%
“…WIPI1, SPHKAP and NCOR1, have recently been associated with anencephaly) [7,16]. These insights add to our existing knowledge of the genetic mechanisms underlying NTDs development [17]. The ongoing genomic revolution will indeed offer the possibility to carry out genomic projects, with the aim of identifying new variants implicated in the biologic basis of NTDs [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Whole exome sequencing (WES) studies on cohorts of patients with NTD have successfully identified genes that contribute or increase the risk of NTD, but have not revealed many monogenic diseases. 7,8 One gene that has been extensively studied in multiple model organisms and has been found to be important in neural tube closure is SHROOM3. Two separate mouse models with loss of function alleles in SHROOM3 have previously been described.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormality can be considered as a disorder of neural tube formation, the most common congenital abnormality with varying prevalence dependent upon race and country. Disorders of neural tube formation are related to genetic but also to environmental factors [5,6]. This holds also true for an appendix of the spinal cord.…”
Section: Introductionmentioning
confidence: 93%